PELATIHAN BUDIDAYA TANAMAN HIDROPONIK BAGI IBU RUMAH TANGGA KELURAHAN KEDUNGSARI KECAMATAN SUKAJADI KOTA PEKANBARU - Wiyati, Rita; Liviawati, Liviawati; Wardi, Jeni (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
Kedungsari sub-district is the most densely populated area in Sukajadi sub-district, if housewives want to do cultivation such as making a living pharmacy or gardening vegetables it is not possible because of the unavailability of land for farming. Kedungsari Village is currently actively increasing the activities of PKK women where women are grouped into business groups where most of the members are housewives. Starting from a meeting with one of the PKK administrators in the village, he also said that the Kedungsari village had never received an understanding of plant cultivation with water media or often called hydroponics. The purpose of holding this community service is that partners are expected to be able to plant and breed vegetable crops with hydroponic media and can take advantage of their harvests for families and to be marketed to outside parties. This activity empowers group members to support the family's economy through mentoring and counseling about hydroponic plant cultivation. The purpose of this activity is that participants are taught how to breed and grow vegetable crops using hydroponic media. The strategy used is to provide knowledge and understanding of hydroponic plant procedures by utilizing a narrow yard. All participants in this activity were women from Kedungsari Village, Sukajadi Subdistrict, Pekanbaru City, which was attended by 20 participants. In understanding and using a narrow yard to grow crops with hydroponic planting media, local residents are very motivated, enthusiastic and creative by using used plastic bottles, as well as using a simple planting media module, residents can easily practice it in their yard. Apart from that, partners can also take advantage of their plant products to be marketed to other parties.